2013
DOI: 10.1515/jpm-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for unfavorable pregnancy outcome in women with adverse childhood experiences

Abstract: Aims: To explore the association between childhood sexual abuse (CSA), physical abuse, as well as other adverse childhood experiences (ACE), and different obstetrical risk factors/behaviors. Methods: In this cohort study, obstetrical risk factors and perinatal outcome in 85 women exposed to CSA were compared to 170 matched unexposed women. CSA, physical abuse, and ACE were explored by face-to-face interviews and by questionnaire. Data on perinatal outcome were extracted from medical charts. Fisher's exact, χ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
7
62
1
2
Order By: Relevance
“…As in other studies, 7 we found that CSA was associated with depressive (OR = 2.60) and anxiety symptoms (OR = 2.58). These associations remained significant even after adjusting for mediating and confounding factors.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As in other studies, 7 we found that CSA was associated with depressive (OR = 2.60) and anxiety symptoms (OR = 2.58). These associations remained significant even after adjusting for mediating and confounding factors.…”
Section: Discussionsupporting
confidence: 88%
“…As a whole, this work has found that having a history of childhood physical abuse (CPA) and/or sexual abuse (CSA) is related to suicidal ideation and/or suicide attempts during pregnancy. 1,7 However, findings have been mixed regarding the relationship between childhood abuse and increased risk of prenatal depression or anxiety. Leeners et al 6 conducted a systematic literature review in 2006 and concluded that pregnant women with a history of CSA were more likely to experience depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that information about accumulated ACE in early pregnancy could be useful to identify women who are at risk of developing pain with higher intensity and large distributions later on, as these are known risk factors for transition to chronic pain (19)(20)(21). In addition, among women with pain during pregnancy, information about ACE is warranted because of previously described unfavorable pregnancy outcomes (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…Among pregnant women exposed to childhood sexual abuse more obstetrical complications, backache, headache and leg cramps were reported during pregnancy and their risk of being hospitalized or of giving birth preterm was increased (9,10). In a small case-control study childhood abuse, including sexual and physical abuse, was reported to influence obstetric and neonatal complications such as preterm birth, depression and suicidal ideation (11). In the same study and in two large cohort studies it was reported that among pregnant women childhood sexual abuse was a traumatic event with greater negative long-term effects than other traumatic events (9,12,13).…”
Section: Introductionmentioning
confidence: 99%